A circular RNA derived from the insulin receptor locus protects against doxorubicin-induced cardiotoxicity . (27th June 2022) - Lu, Dongchao; Chatterjee, Shambhabi; Xiao, Ke; Riedel, Isabelle; Huang, Cheng-Kai; Costa, Alessia; Cushman, Sarah; Neufeldt, Dimyana; Rode, Laura; Schmidt, Arne; Juchem, Malte; Leonardy, Julia; et al.
Abstract: Aims: Cardiotoxicity leading to heart failure (HF) is a growing problem in many cancer survivors. As specific treatment strategies are not available, RNA discovery pipelines were employed and a new and powerful circular RNA (circRNA)-based therapy was developed for the treatment of doxorubicin-induced HF. Methods and results: The circRNA sequencing was applied and the highly species-conserved circRNA insulin receptor (Circ-INSR) was identified, which participates in HF processes, including those provoked by cardiotoxic anti-cancer treatments. Chemotherapy-provoked cardiotoxicity leads to the down-regulation of Circ-INSR in rodents and patients, which mechanistically contributes to cardiomyocyte cell death, cardiac dysfunction, and mitochondrial damage. In contrast, Circ-INSR overexpression prevented doxorubicin-mediated cardiotoxicity in both rodent and human cardiomyocytes in vitro and in a mouse model of chronic doxorubicin cardiotoxicity. Breast cancer type 1 susceptibility protein (Brca1) was identified as a regulator of Circ-INSR expression. Detailed transcriptomic and proteomic analyses revealed that Circ-INSR regulates apoptotic and metabolic pathways in cardiomyocytes. Circ-INSR physically interacts with the single-stranded DNA-binding protein (SSBP1) mediating its cardioprotective effects under doxorubicin stress. Importantly, in vitro transcribed and circularized Circ-INSR mimics also protected against doxorubicin-induced cardiotoxicity. Conclusion: Circ-INSR is a highly conserved non-coding RNA which is down-regulated during cardiotoxicity and cardiac remodelling. Adeno-associated virus and circRNA mimics-based Circ-INSR overexpression prevent and reverse doxorubicin-mediated cardiomyocyte death and improve cardiac function. The results of this study highlight a novel and translationally important Circ-INSR-based therapeutic approach for doxorubicin-induced cardiac dysfunction. Structured Graphical Abstract: Structured Graphical Abstract Circular RNA therapy for cardioprotection. AAV, adeno-associated virus; INSR, insulin receptor; SSBP1, single-stranded DNA-binding protein.